Preparation of Calcinite Fertilizer from Golden Snail Shells by Calcination and Crystallization Processes - Nur Halizah Hadi; M. Hadid Muhaimin; Sri Redjeki (Advance Sustainable Science Engineering and Technology, 2024)
The golden apple snail is a significant pest that damages crops and can lead to crop failure because it has a habit of consuming various soft plants, including young rice plants. Golden snail shells have a high calcium carbonate content of around 60.56%. Large calcium content can be used as a source for the production of calcium nitrate fertilizer. The stages in making calcinit fertilizer are washing the shell of gold snails and drying for 1-2 days. After that, size reduction is carried out to 50 mesh. After that, the calcination process was carried out with a variable temperature of 700,750,800,850,900 ℃ for 4 hours. The calcined shell is dissolved with HNO3 with a variable of 1-5 N for 1 hour. After that the solution is filtered from impurities and neutralized to pH 7. After that the solution is crystallized into white crystals. The largest Ca and N content was obtained at a calcining temperature of 900 and HNO3 5 N concentrations, namely Ca of 21.94% and N of 16.52%. The results showed that the higher the calcining temperature and the higher the HNO3 content, the higher the Ca content and N content